Comparison of CD4 and CD8 counts and ratio in HIV negative pulmonary tuberculosis patients with normal healthy controls - Sabhapandit, Debahuti; Hazarika, Plabon; Phukan, Anil C.; Lynrah, K. G.; D., Elantamilan (International Journal of Research in Medical Sciences, 2017)
Background: There is an equivocal contention that Tuberculosis may be a cause of non-HIV-associated CD4+ T cell lymphopenia. In HIV negative patients, CD4+ and CD8+ T cell count suppression has been associated with TB infection. Prediction of HIV coinfection in newly diagnosed pulmonary TB patients with negative HIV status by estimation of CD4, CD8 count and CD4:CD8 ratio. Methods: Newly diagnosed pulmonary TB patients comprising of 30 numbers with negative HIV status were subjected for estimation of CD4, CD8 counts and ratio for prediction of HIV coinfection. Equal number of healthy controls was also included in the study for comparison of the values. Results: Significantly lower CD4 and CD8 counts among pulmonary TB infected HIV negative patients as compared with healthy controls was found. The CD4:CD8 ratio was normal when compared with healthy controls. Conclusions: The present study highlights the importance of estimation of CD4+ and CD8+ T cell counts and ratio in newly diagnosed pulmonary TB patients with negative HIV status. Prediction ability in combination with early detection and appropriate management play major role in evading emergence of drug resistance among the HIV-TB coinfected patients.